Global patterns of leaf mechanical properties - Onoda, Yusuke; Westoby, Mark; Adler, Peter B; Choong, Amy M.F; Clissold, Fiona J; Cornelissen, Johannes H.C; Díaz, Sandra; Dominy, Nathaniel J; Elgart, Alison; Enrico, Lucas; Fine, Paul V.A; Howard, Jerome J; et al. (Ecology letters, 2011)
Ecology Letters (2011) 14: 301-312 ABSTRACT: Leaf mechanical properties strongly influence leaf lifespan, plant-herbivore interactions, litter decomposition and nutrient cycling, but global patterns in their interspecific variation and underlying mechanisms remain poorly understood. We synthesize data across the three major measurement methods, permitting the first global analyses of leaf mechanics and associated traits, for 2819 species from 90 sites worldwide. Key measures of leaf mechanical resistance varied c. 500-800-fold among species. Contrary to a long-standing hypothesis, tropical leaves were not mechanically more resistant than temperate leaves. Leaf mechanical resistance was modestly related to rainfall and local light environment. By partitioning leaf mechanical resistance into three different components we discovered that toughness per density contributed a surprisingly large fraction to variation in mechanical resistance, larger than the fractions contributed by lamina thickness and tissue density. Higher toughness per density was associated with long leaf lifespan especially in forest understory. Seldom appreciated in the past, toughness per density is a key factor in leaf mechanical resistance, which itself influences plant-animal interactions and ecosystem functions across the globe.